Modern technologies of microbiological research in ophthalmology. Part 2 - O.V. Shilovskikh; V.O. Ponomarev; V.N. Kazaikin; A.N. Kulikov; N.S. Demchenko; K.A. Tkachenko; S.M. Rozanova (Офтальмохирургия)
Purpose. To highlight modern microbiological technologies (mass spectrometry, polymerase chain reaction (PCR), sequencing, laser light scattering) and methods (phenotypic, genetic, analytical methods) for detecting antibiotic sensitivity. Material and methods. To complete this review, a search was carried out for scientific publications of domestic and foreign authors on the resources of PubMed, Medline, eLibrary from 2008 to 2021, devoted to the currently existing methods for determining sensitivity to antibiotics with an emphasis on ophthalmological microbiological diagnostics. Results. Modern technologies make it possible to determine the presence of resistance to specific drugs and additionally reveal its mechanisms, allow direct detection of components of microorganisms responsible for the loss of sensitivity to antibiotics.Conclusion. The modern microbiological technologies presented in the review for determining antibiotic resistance make it possible not only to solve the clinical tasks of treating specific patients in the shortest possible time, but also to carry out epidemiological monitoring to explain the mechanisms leading to the antibiotic resistance in the population at the proteomic and genomic levels.